Improving safety of laparoscopic cholecystectomy with use of pre operative magnetic resonance cholangiopancreatography for management of patients with gall stones - Jadaon, Abhiyutthan Singh; Singh, Chandra Pal; Champawat, Chitra (International Surgery Journal, 2025)
Background: Laparoscopic cholecystectomy (LC) is the gold standard surgical treatment of cholelithiasis. However, this surgery has its own known complications. Assessment of patients with preoperative MRCP for anatomical anomaly in biliary tree and common bile duct stones (CBDs), can prevent intraoperative and post operative complications. Methods: Authors conducted retrospective randomized study at Kota Heart Hospital, Kota, Rajasthan between January 2014 and December 2024. Patients with the presence of symptomatic cholecystolithiasis undergoing LC without signs (i.e., jaundice) of cholestasis were included in our study. Patients were divided into two groups; Group I included 696 patients in whom pre-operative MRCP followed by laparoscopic cholecystectomy was done . Group II included 290 patients who underwent laparoscopic cholecystectomy and routine MRCP was omitted in their pre-operative workup. We measured intraoperative biliary injury and the incidence rate of postoperative complications in this study. Results: The Study showed that all patients in Group I revealed smooth post-operative period and no incidence of residual CBD calculi. In group II, 9 patients developed early bile leakage and one developed jaundice after 7 months. Preoperative MRCP was able to diagnose biliary radicles abnormalities in 8 patients (1.1%) of group 1. Also the course of cystic duct was diagnosed tortuous in 29 cases (4.1%) of group 1. Conclusions: Preoperative MRCP helps in visualization of the extrahepatic biliary tree and in identifying CBD stones. This provides surgeon information about possible anatomical variations. Which leads to decrease in incidence of intraoperative complications and residual CBD stones.